Illumination‐Induced Hole Doping for Performance Improvement of Graphene/n‐Silicon Solar Cells with P3HT Interlayer. (10th February 2017) - Xu, Dikai; He, Jian; Yu, Xuegong; Gao, Dace; Ma, Lingling; Mu, Xinhui; Zhong, Mengyao; Xu, Yang; Ye, Jichun; Xu, Mingsheng; Yang, Deren
Abstract : Graphene/silicon (Gr/Si) solar cells have triggered considerable interest for their potential in low‐cost and high‐efficiency photovoltaic applications. However, the performance of Gr/Si solar cells is still limited by poor Gr conductivity and carrier recombination at the interface. In this study, a solution‐processable poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) thin film is employed as a carrier selective interlayer in the graphene and n‐type Si solar cells, which can increase the work function and conductivity of the Gr due to photoinduced p‐type doping under light illumination. Consequently, the Schottky barrier height of the solar cells is enhanced, whereas the carrier recombination at the interface is suppressed. The utilization of antireflection and additional chemical doping at the other side of the Gr layer further improves the performance of the solar cells, which shows a power conversion efficiency of 12.95% with high stability. This study paves a new venue for the development of Gr/Si solar cells toward real applications. Abstract : An illumination‐induced p‐type doping is demonstrated in graphene/P3HT/n‐silicon solar cells, where the P3HT film acts as an interlayer and a photoinduced dopant of graphene. Employment of dual‐side doping strategy and antireflection coating leads to the solar cells with an efficiency of 12.95% and great stability.